Hopes and Fears for Art - Morris, William, 1834-1896 (Salt Lake City, UT : Project Gutenberg, 2003)
"Hopes and Fears for Art" by William Morris is a collection of lectures delivered in the late 19th century. The work primarily explores the importance of decorative arts and their relationship to daily life, the labor process, and society as a whole. Morris highlights the need for art to be accessible and meaningful to the general populace, rather than being confined to the elite or existing solely for decorative purposes. The opening of the text sets the stage for Morris' exploration of art and its significant impact on human existence. He emphasizes that while the so-called "greater arts" like architecture, painting, and sculpture may be noble, they have become divorced from the more practical, decorative arts that fill everyday life with beauty and meaning. Morris argues for a reintegration of these arts with daily labor and stresses that the creation of beauty in work enhances the dignity of labor itself. He challenges the current state of art, which he perceives as declining into triviality, and expresses a hopeful vision for the future where art and craftsmanship can regenerate and inspire a collective appreciation for beauty in life. (This is an automatically generated summary.)
The lesser arts -- The art of the people -- The beauty of life -- Making the best of it -- The prospects of architecture in civilization.
Release date is 2003-02-01
Transcribed from the 1919 Longmans, Green and Co. edition by David Price
Keywords: Art; Arts and crafts movement